Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jpen.1773
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Chain Polyunsaturated Fatty Acids and Lipid Peroxidation Products in Donor Human Milk in the United Kingdom: Results From the LIMIT 2‐Centre Cross‐Sectional Study

Abstract: Background: Donor human milk (DHM) is used as alternative to maternal milk to feed preterm infants; however, it may provide less long-chain (LC) polyunsaturated fatty acids (PUFAs) and more oxidized lipids, which may be detrimental to preterm infant health and development. Levels have not been reported for DHM in the United Kingdom. Methods: DHM (n = 19) from 2 neonatal units, preterm milk from a neonatal unit (n = 10), and term milk from the community (n = 11) were analyzed for fatty acids, malondialdehyde, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The baseline level of MDA was somewhat higher in our study and our results on 4-HNE at baseline was comparable to that of Nessel et al [31] who compared donor human milk with term and preterm milk by measuring lipid peroxidation markers including MDA and 4-HNE. The infants included in their study were somewhat more mature (30 weeks + 6 days vs. 28 weeks + 2 days) and there was no information on the type of breast milk in relation to the time after delivery.…”
Section: Lipid Peroxidessupporting
confidence: 90%
“…The baseline level of MDA was somewhat higher in our study and our results on 4-HNE at baseline was comparable to that of Nessel et al [31] who compared donor human milk with term and preterm milk by measuring lipid peroxidation markers including MDA and 4-HNE. The infants included in their study were somewhat more mature (30 weeks + 6 days vs. 28 weeks + 2 days) and there was no information on the type of breast milk in relation to the time after delivery.…”
Section: Lipid Peroxidessupporting
confidence: 90%
“…There are currently no guidelines for safe intake ranges of lipid peroxidation products in preterm infants, and the levels of TBARS and HNE found in FM are lower than the levels previously reported in UK preterm breast milk and donor human milk by ourselves 13 . Other studies have similarly found higher lipid peroxidation in fresh Italian term breast milk than term FM, 22 although this observation is not universal, with lower levels in fresh Spanish and American term breast milk than in term and preterm FM, respectively 7,24 .…”
Section: Discussionmentioning
confidence: 58%
“…Fatty acids were analysed as described previously, 13 with tricosanoic acid as internal standard, using gas chromatography (7820A; Agilent Technologies, Santa Clara, CA, USA) and Omegawax™ 100 column (15 m × 0.1 mm × 0.5 µm; Sigma‐Aldrich, Poole, UK).…”
Section: Methodsmentioning
confidence: 99%
“…PUFAs are essential nutrients for the human body and will cause various diseases if they are lacking. PUFAs can thus be used as nutritional supplements in different food and beverages (Simopoulos, 2000;Nessel et al, 2020). In medicine, PUFAs serve a variety of physiological functions such as anti-inflammation and blood lipid regulation while also necessary for the prevention of cardiovascular diseases and treating schizophrenia (Marion-Letellier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%